STRATEGY OF PARTNERSHIP BETWEEN RUSSIA AND THE EU AT THE CURRENT STAGE - Zelimkhan H. Gaysumov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
Until recently Russian policy for the European Union (EU) differed in uncertainty: on the one hand, the EU was perceived as one of many democratic institutes of Europe which also Russia by an example of the majority of the European countries could enter, with another - process of the European integration was perceived as the phenomenon minor in the Russian policy as traditionally Russia was guided by the bilateral relations with the European states, first of all with Germany, France and Great Britain which were perceived as worthy partners for dialogue. In article answers to the topical issues connected with ways of strengthening of partnership between the states are analyzed. Prerequisites of development of the relations between Russia and the EU in various fields of activity come to light. The author the essence of the main problems arising on the way of cooperation between Russia and the EU locates and proposals on prevention of the reasons of emergence of problem situations are made.